2016
DOI: 10.1016/j.aop.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A difference-equation formalism for the nodal domains of separable billiards

Abstract: Recently, the nodal domain counts of planar, integrable billiards with Dirichlet boundary conditions were shown to satisfy certain difference equations in [Ann. Phys. 351, 1 (2014)]. The exact solutions of these equations give the number of domains explicitly. For complete generality, we demonstrate this novel formulation for three additional separable systems and thus extend the statement to all integrable billiards.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Within each class, it was shown that the number of domains, ν m,n for one eigenfunction is related to ν m+2n,n by a difference equation [9,7]. We can, in fact, write down the operator (in the matrix form) which actually takes us along the ladder of states beginning with ψ m,n , up and down.…”
Section: Right Isosceles Trianglementioning
confidence: 99%
See 4 more Smart Citations
“…Within each class, it was shown that the number of domains, ν m,n for one eigenfunction is related to ν m+2n,n by a difference equation [9,7]. We can, in fact, write down the operator (in the matrix form) which actually takes us along the ladder of states beginning with ψ m,n , up and down.…”
Section: Right Isosceles Trianglementioning
confidence: 99%
“…There are some very interesting connections between exactly solvable models and random matrix theories, a summary may be seen in [6]. The Helmholtz operator is separable in certain coordinate systemsfor these cases, the solutions can be found [7]. The non-separable problems for which the classical dynamics is integrable have been recently studied in detail [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations